Abrupt transition to irreversible damage in the overdrafted Sacramento Valley aquifer system - Stacy Larochelle; Kristel Chanard; Manon Dalaison; Jerome Fortin; Romain Jolivet; Laurent Longuevergne; Luce Fleitout; Donald F. Argus; Louis-Marie Gauer; Jean-Philippe Avouac (Proceedings of the National Academy of Sciences, 2026)
Groundwater extraction decreases water pressure in aquifer systems, causing reversible or irreversible deformation of the water-bearing layers that manifests as recoverable or permanent displacements of the land surface, respectively. Detecting and forecasting when and where an aquifer system transitions from a reversible, poroelastic regime, to an irreversible, inelastic regime remains a crucial challenge given the complex, heterogeneous nature of aquifer systems. Here we leverage high-resolution measurements of ground deformation and groundwater levels from 2016 to 2022 to characterize both regimes at the regional scale and show that a critical transition occurred in large areas of the Sacramento Valley during California’s 2020–2022 extreme drought. Our analysis reveals that, while deformation remained primarily poroelastic during the 2016–2020 interdrought period, land subsidence in areas of intense groundwater extraction accelerated abruptly in 2021, with subsidence rates exceeding the inferred poroelastic rates by several decimeters per year. Such rapid and extensive land subsidence indicates severe inelastic compaction and loss of storage capacity of the underlying aquifer system, which pose a serious threat to California’s water resources and infrastructure. A comparison of present-day deformation with historical groundwater levels reveals that this abrupt transition was not predictable based on the available groundwater records alone.